Research on Suzhou-Hangzhou Paradigm in Tang Poetry from the Perspective of Literary Cartography (Global Journal of Human-Social Science, 2023)
Bai Juyi s poems in Suzhou and Hangzhou represented the turn of Bai Juyi s poetry creation from the outside to the inside He expressed his daily life deeply in these poems The research on Bai Juyi s poems and essays in Suzhou and Hangzhou has the following values The research explored the historical origin and cultural deposits behind every poem of Bai Juyi in Suzhou and Hangzhou From the perspective of time the changes of ancient and modern poems reflected the historical changes From the spatial dimension the poem map reflected the distribution of relics The research revealed the connotation and significance of various types of Bai Juyi s poems in Suzhou and Hangzhou The research also revealed Bai Juyi s interactive writing style regional connection and historical shuttle Last but not least we should sum up the paradigm of Suzhou and Hangzhou in Tang poetry
Keywords: bai juyi; literary cartography; suzhouhangzhou paradigm; tang poetry